The Influence of Digital Marketing and Electronic Word of Mouth (E-WOM) on Purchasing Decisions for Wardah Lipstick Product in Surabaya - Mutma'innah, Lail Nasru; Soebiantoro, Ugy (PT Larva Wijaya Penerbit, 2025)
This research is intended to analyze the influence of digital marketing and e-WOM on purchasing decisions of Wardah Lipstick products in Surabaya. The research adopted a quantitative method with a causal associative design. Primary data was sourced from 98 respondents using an online questionnaire and purposive sampling. The Data were examined through the Partial Least Square (PLS) method with SmartPLS software, including both outer model and inner model assessments. Findings reveal that digital marketing had a favorable and significant impact on consumer purchase decisions, with accessibility identified as the most dominant indicator. Furthermore, e-WOM also affects buying behavior in a positive and significant manner, with valence of opinion serving as the dominant indicator. These results highlight that the combination of effective digital marketing strategies and positive consumer reviews can strengthen consumer purchasing decisions toward local cosmetic products.